Segregation but Not Replication of the Pseudomonas aeruginosa Chromosome Terminates at Dif - Bijit K. Bhowmik (American Society for Microbiology, 2018)
ABSTRACT Coordination between chromosome replication and segregation is essential for equal partitioning of genetic material between daughter cells. In bacteria, this is achieved through the proximity of the origin of replication, oriC, and the chromosome partitioning site, parS. We report here that in Pseudomonas aeruginosa, segregation but not replication is also controlled at the terminus region of the chromosome. Using the fluorescent repressor operator system (FROS), we investigated chromosome segregation in P. aeruginosa strain PAO1-UW, wherein the chromosome dimer resolution site, dif, is asymmetrically positioned relative to oriC. In these cells, segregation proceeded sequentially along the two chromosomal arms and terminated at dif. In contrast, chromosome replication terminated elsewhere, opposite from oriC. We further found two large domains on the longer arm of the chromosome, wherein DNA segregated simultaneously. Notably, GC-skew, which reflects a bias in nucleotide usage between the leading and lagging strands of the chromosome, switches polarity at the dif locus but not necessarily at the terminus of replication. These data demonstrate that termination of chromosome replication and segregation can be physically separated without adverse effects on bacterial fitness. They also reveal the critical role of the dif region in defining the global layout of the chromosome and the progression of chromosome segregation and suggest that chromosome packing adapts to its subcellular layout. IMPORTANCE Segregation of genetic information is a central event in cellular life. In bacteria, chromosome segregation occurs concurrently with replication, sequentially along the two arms from oriC to dif. How the two processes are coordinated is unknown. We explored here chromosome segregation in an opportunistic human pathogen, Pseudomonas aeruginosa, using its strain with markedly unequal chromosomal arms. We found that replication and segregation diverge in this strain and terminate at very different locations, whereas the longer chromosomal arm folds into large domains to align itself with the shorter arm. The significance of this research is in establishing that segregation and replication of bacterial chromosomes are largely uncoupled from each other and that the large-scale structure of the chromosome adapts to its subcellular layout.